THE EFFECT OF INFLATION, EDUCATION LEVEL, AND LABOR FORCE PARTICIPATION LEVEL ON POVERTY LEVEL IN NORTH SUMATRA PROVINCE - Nabila Ramadina; Reza Juanda; Aulia Maharani Br Purba (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the effect of inflation, education level, and labor force participation rate on the poverty rate in North Sumatra Province during 2005–2024. The study uses secondary time-series data obtained from the Central Statistics Agency (BPS) of North Sumatra Province. The analytical method is multiple linear regression using EViews 13. The results show that inflation has a positive and significant effect on the poverty rate, while education level and labor force participation rate have negative and significant effects. Simultaneously, inflation, education level, and labor force participation rate significantly affect the poverty rate. The adjusted R-squared of 0.810563 indicates that 81.05 percent of the variation in poverty is explained by the three independent variables, while the remaining 18.95 percent is explained by other factors outside the model.